Microscopic colitis in patients presenting with chronic diarrhea - Misra Vatsala; Misra S; Dwivedi Manisha; Singh Premala; Agarwal Varsha (Indian Journal of Pathology and Microbiology, 2010)
Aim: To investigate the prevalence of microscopic colitis among patients presenting with chronic watery diarrhea. Material and Methods: Colonic biopsies from 400 patients presenting with chronic watery diarrhea and other symptoms pertaining to lower gastrointestinal tract were studied. After a detailed clinical history and thorough physical examination full length colonoscopy was done using flexible colonoscope. Colonic biopsies were taken from abnormal and normal areas. Three to five micron thick sections were cut and stained with hematoxylin and eosin and Masson′s trichrome stain to highlight sub epithelial collagen. Results: Fifteen out of 400 (3.7%) colonic biopsies from patients presenting with chronic diarrhea had evidence of microscopic colitis. Five out of fifteen biopsies (33%) were diagnosed as collagenous colitis, 10 biopsies (67%) had evidence of lymphocytic colitis; 14/400(3.5%) histologically normal biopsies were taken as controls to compare various demographic and risk factors. Ten out of 15 patients (67%) were clinically diagnosed as irritable bowel syndrome. In the remaining five an infective etiology was suspected. On colonoscopy12/15 (80%) had no abnormality and 3/15 (20%) had mild hyperemia. Conclusion: A possibility of microscopic colitis should be considered while examining colonoscopic biopsy of a patient with chronic watery diarrhea and normal colonoscopy to avoid the misdiagnosis that may affect the treatment of patients